IODIVERSITY PATTERNS AND SEASONAL VARIATIONS OF ENTOMOFAUNA ACROSS DIVERSE ECOSYSTEMS IN SOUTHERN TAMIL NADU (International Journal of Food and Nutritional Sciences, 2023)
This study examines the biodiversity and seasonal variations of entomofauna across diverse ecosystems in southern Tamil Nadu. Using standardized sampling across forest, wetland, agricultural, and scrubland ecosystems, the study identifies significant variations in entomofauna biodiversity due to seasonal changes. Key findings reveal ecosystem-specific patterns and the importance of preserving high-diversity areas. The implications for conservation and ecosystem management are discussed, contributing to broader ecological studies on tropical entomofauna diversity.